1. The problem statement, all variables and given/known data Say you have: EQ1: y1''*t+y1'*t+y2=0 and EQ2: y2''*t+y2'*t+y1=0 y1(0)=0,y1'(0)=0,y2(0)=0,y2'(0)=0 2. Relevant equations 3. The attempt at a solution I can get it so far, but having both y1 and y2 really gives me fits: Eq1: Y1(-2s-1)+dY1/ds(-s2-s)=-Y2 Eq2: Y2(-2s-1)+dY2/ds(-s2-s)=-Y1 I try to shift it around to be dY1/Y1 = (-2s-1)/(-s2-s)-Y2/Y1(-s2-s) But then I just don't know to do the integrations given you have both Ys. I just can't separate them. Any help would be appreciated.